ANALISIS OPERASIONAL PELAYANAN TERHADAP PENDAFTARAN PASIEN DI RUMAH SAKIT UMUM DR.WAHIDIN SUDIRO HUSODO - Arifin, Syamsul; Setyoaji, Givanola Tri; Anisa, Nur Aini; Siswohadi, Siswohadi (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2021)
This research aims to describe the effect of operational services on outpatient registration in RSU Dr. Wahidin Sudiro Husodo, Mojokerto. Getting health services is one of the basic rights of the Indonesian population, in addition to education services, legal protection, easy health services are also expected to improve the level of public health. RSU Dr. Wahidin Sudiro Husodo, Mojokerto is one of the government services that provides services in health. The purpose of this study is to describe the health quality of service to the registration of outpatients in the RSU Dr. Wahidin Sudiro Husodo, Mojokerto. To find out how the quality of service to the registration of outpatients in RSU dr. Wahidin Sudiro Husodo, Mojokerto, five dimensions of quality used, real, reliability, responsive processes, certainty, and empathy. The study uses qualitative methods and is a type of descriptive research. The location of the study was RSU Dr. Wahidin Sudiro Husodo, Mojokerto. Outpatient registration staff are used as informants in accordance with the job description at RSU Dr. Wahidin Sudiro Husodo, Mojokerto. Data is being collected by observing, in-depth interviews and documentation. Data analysis was performed using data reduction, data review, and conclusions. Research shows that the quality of health services in the RSU dr. Wahidin Sudiro Husodo, Mojokerto to customers who experienced the services provided were able to provide satisfaction.